2016
DOI: 10.1161/circulationaha.116.021314
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Estimated 10-Year Risk of Recurrent Vascular Events and Residual Risk in a Secondary Prevention Population

Abstract: Among patients with vascular disease, there is very substantial variation in estimated 10-year risk of recurrent vascular events. If all modifiable risk factors were at guideline-recommended targets, half of the patients would have a 10-year risk <10%. These data suggest that even with optimal treatment, many patients with vascular disease will remain at >20% and even >30% 10-year risk, clearly delineating an area of substantial unmet medical need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 38 publications
3
132
1
11
Order By: Relevance
“…Additional scores developed for secondary prevention in patients with established cardiovascular disease (CVD) do not include obstructive CAD as a variable, but were developed in populations dominated by obstructive CAD,63, 65, 66, 67, 68, 69, 70, 71 and therefore are of unknown appropriateness for stable INOCA patients.…”
Section: Secondary Prevention Risk Scoresmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional scores developed for secondary prevention in patients with established cardiovascular disease (CVD) do not include obstructive CAD as a variable, but were developed in populations dominated by obstructive CAD,63, 65, 66, 67, 68, 69, 70, 71 and therefore are of unknown appropriateness for stable INOCA patients.…”
Section: Secondary Prevention Risk Scoresmentioning
confidence: 99%
“…The Second Manifestation of Arterial Disease (SMART),69 Thrombolysis In Myocardial Infarction Risk Score for Secondary Prevention (TIMI‐TRS2 o P),70 and A Coronary Disease Trial Investigating Outcome with Nifedipine (ACTION) risk66 scores, all showed substantial variability in risk among patients with stable CVD, but more importantly that aggressive guideline treatment in high‐risk patients decreased their risk 69. Similarly, the PREDICT CVD (New Zealand Primary Care Cohort Study) score developed for patients with previous CVD recognizes patient‐specific risks of future events and how they may be reduced through therapeutic and behavioral strategies 68…”
Section: Secondary Prevention Risk Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with a clinical manifestation of cardiovascular disease show substantial variation in cardiovascular prognosis 1. Similar to the primary prevention setting, decisions on initiation or intensification of preventive treatment should be based on anticipated clinical benefit derived from prediction models, rather than based on the level of individual cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%